USING RECIPROCAL TEACHING (RT) STRATEGY TO IMPROVE THE ABILITY OF THE FIRST YEAR STUDENTS OF SMA NEGERI 2 TANDUN IN COMPREHENDING NARRATIVE TEXTS - Trianingsih '; Jismulatif '; M. Syarfi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. This paper was aimed at finding out to what extent reciprocal teaching could improve the ability of the first year students of SMA Negeri 2 Tandun, Rokan Hulu, Riau in comprehending narrative texts. The participants of this research were 32 students of the first year students of SMA Negeri 2 Tandun, Rokan Hulu, Riau. This research was conducted in 2 cycles. The data were collected through (1)observation sheet which was applied to know the students’ activities during teaching and learning process, (2) objective test was done to measures students’ achievement, and (3) field note was done to obtain information about teacher, the students’ activities and teacher’s performance during the implementation of reciprocal teaching. The research findings can be briefly explained as follows; firstly, the students’ ability in comprehending narrative texts could be improved by using reciprocal teaching. Before the research was done, the mean score of students’ pre-test was 60.94, up to 68.02 in the post-test 1, and up again to 75.21 in the post-test 2. After the research has done for cycle 1, the mean score of students’ reading ability was 68.02. In the cycle 2, it increased up to 75.21. Secondly, the students’ activeness increased from cycle 1 to cycle 2. This improvement happened because this reading comprehension strategy was appropriate to be implemented to the class.Keyword : Reciprocal Teaching, Reading, Narrative Text